Reply to Second comment on ‘The climate mitigation gap: education and government recommendations miss the most effective individual actions’ - Seth Wynes; Kimberly A Nicholas (Environmental Research Letters, 2018)
In their comment piece, Laycock and Lam ( Environ. Res. Lett. 13 068001) focused on the importance for reducing emissions of actions beyond individual choices and overconsumption, and raise the issue of family planning as a human right. Here we respond that both individual and collective actions, in private and professional life, are important to reducing emissions to near zero in the next few decades. While we do not argue that individual actions will be sufficient to achieve this profound transformation, we believe that they can be helpful towards this goal, and also note from our own observations that we see personal, professional, and collective actions as often mutually reinforcing rather than contradictory. Regarding overconsumption, we reiterate that our study was designed to illustrate the decisive role that consumption patterns play in driving greenhouse gas emissions, based on the understanding that wealthy, high-carbon individuals are responsible for a disproportionately large share of emissions. Regarding the ethics of family planning, we fully agree with Laycock and Lam (and international agreements) that family planning is a private decision. We give examples of our careful public communication around this issue to provide this context and thank them for the opportunity to do so. In their comment piece, Laycock and Lam provide insight into the discussion of high-impact climate actions, especially concerning the effect of communicating about family size. Here we respond to their thoughts on the scope of our research, including (1) the importance of actions beyond the private individual level, (2) the importance of overconsumption to an individual’s emissions and (3) the ethics of communications pertaining to the planning of family size.